1997
DOI: 10.1074/jbc.272.37.23239
|View full text |Cite
|
Sign up to set email alerts
|

Topology of the Integral Membrane Form of Escherichia coli SecA Protein Reveals Multiple Periplasmically Exposed Regions and Modulation by ATP Binding

Abstract: SecA insertion and integration into the Escherichia coli inner membrane is a critical step for the catalysis of protein translocation across this layer. To understand this step further, SecA topology was investigated. To determine which regions of SecA are periplasmically exposed, right-side out membrane vesicles were prepared from strains synthesizing monocysteine SecA variants produced by mutagenesis and probed with a membrane-impermeant sulfhydryl-labeling reagent. To determine which regions of SecA contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
114
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(121 citation statements)
references
References 53 publications
4
114
0
3
Order By: Relevance
“…Studies from a variety of groups over the past decade have revealed that SecA is a multidomain protein that can exist as a monomer or a dimer, and that its domain rearrangements can be triggered by binding to any of its several ligands. 67,[69][70][71][72][73][74][75][76][77][78][79][80][81] The key to the conformational rearrangements appears to be intramolecular interactions that stabilize a more tightly packed, ''closed'' form of the protein. Weakening these interactions relieves these intramolecular constraints, and the protein domains partially dissociate, creating a less tightly packed, ''open'' form of the protein.…”
Section: Seca Is Central To the Bacterial Sec Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from a variety of groups over the past decade have revealed that SecA is a multidomain protein that can exist as a monomer or a dimer, and that its domain rearrangements can be triggered by binding to any of its several ligands. 67,[69][70][71][72][73][74][75][76][77][78][79][80][81] The key to the conformational rearrangements appears to be intramolecular interactions that stabilize a more tightly packed, ''closed'' form of the protein. Weakening these interactions relieves these intramolecular constraints, and the protein domains partially dissociate, creating a less tightly packed, ''open'' form of the protein.…”
Section: Seca Is Central To the Bacterial Sec Pathwaymentioning
confidence: 99%
“…72,74,75,88 In parallel, this C-terminal region was shown to be the region inserted into the membrane as SecA became a membrane-resident protein. 75,76,79,80 Thus, the picture that emerges is that the ligand-mediated triggering of domain dissociation leads to insertion of SecA into the membrane and activation of its translocase function. Economou's group 69,89 pointed to a specific region near the C-terminus, residues 783-795, that serves as an intramolecular regulator of ATPase activity (IRA1), and proposed that ligands (or deletion) caused the release of this IRA inhibition.…”
Section: Seca Is Central To the Bacterial Sec Pathwaymentioning
confidence: 99%
“…Since the original discovery of SecA (7), it has been known that the protein is distributed in vivo equally between the cytosol and the membrane. Numerous early studies demonstrated that SecA is not simply associated with the membrane translocon via protein-protein interaction, but rather, in vivo, as much as 30% of membraneassociated SecA is integral to the membrane and is resistant to removal by high-salt and urea washes (8)(9)(10)(11)(12)(13). A specific role has not yet been assigned to the integral SecA.…”
mentioning
confidence: 99%
“…The insertion of SecA was originally defined by the in vitro generation of a 30-kDa C-terminal fragment that was protected by membrane from proteolysis (4,6). It was shown later that some N-terminal portions of SecA insert as well, because they were also protected from an external protease (7) or accessible from the periplasmic side (8,9).…”
mentioning
confidence: 99%